An hedperf assessment of marketing, tourism and entrepreneurship education and graduate unemployment in osun state southwest nigeria - E A, Ulabor; A I, Motajo; O B, Osinubi (Journal of Management and Science, 2022)
Entrepreneurship drives both industrial and economic development globally. This is particularly true for marketing and tourism in emerging markets. Evidently, marketing/tourism graduates and entrepreneurs (MTGE) stand better chances in these markets.But MTGEs are yet to profitably and effectively scale the unemployment huddles in Nigeria. This study attempts a qualitative adaptation of Abdullah’s (2006) HEdPERF and Sultan and Wong’s (2011) core quality dimensions to understand why MTGEs are still unable to scale the unemployment huddles. The study posits first that the current perceptions of Marketing, tourism and entrepreneurship education (MTEE) are rather mistaken; MTEE perceptions and expectations are incongruent. Secondly,currents attempts are synonymous with learning to walk before crawling. Thirdly, there are largely mismatches between taught skills and actual market demand. Urgent steps like diligent stock taking, conscientiously imbibing relevant vocations and skills at early learning ages, change in mind set and keenly supervised capacity building programmes for teachers/trainers are suggested.Above all, complete overhaul of the Nigerian entrepreneurship education curricula is deemed prudent. Thus do we submit that we may sow good seeds of MTEE on fertile land and move away from the entrapment of a mono-product economy.